Kisah Adam dalam Al-Quran dan Alkitab Serta Pengaruhnya dalam Tafsir - Muhammad Amin (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article is a comparative study of the story of Prophet Adam in the Koran and the Bible and its influence in the commentaries. By using a comparative approach, the writer compares the narrative description of the story in the Koran and the Bible, and how it influences the interpretation. There are many similarities in the narrative, such as the substance of creation, his placement in heaven, and the prohibition of eating from a tree. On the other hand, there are also many differences related to the details of the story and these differences have a considerable influence in the tafsir of the Koran, as evidenced by the acquisition of various information or history of israiliyyat in interpretive books such as the interpretation of al-Tabari, al-Baidhawi, and al-Kasysyaf.